PENGARUH NET PROFIT MARGIN (NPM) DAN RETURN ON ASSET (ROA)TERHADAP HARGA SAHAM PADA PT. MAYORA INDAH Tbk - Agussalim Rahman; Umar Umar; Jumria Jumria (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
ABSTRACT. The purpose of this study was to determine the effect of Net Profit Margin and Return on Assets on stock prices at PT. Mayora Indah, Tbk. The types of data used are qualitative data and quantitative data. Source of data used is secondary data. The analytical method used is multiple regression analysis. The results showed that the regression equation was Y = 1,809 + 12.58 X1 + 39.94 X2, while the correlation coefficient was 0.260. The coefficient of determination is 6.80%. t calculate Net Profit margin 0.022 <2.353 from t table, meaning that Net Profit Margin has a positive but not significant effect on stock prices at PT. Mayora Indah, Tbk. t calculate Return on Assets 0.084 <t table 2.353, meaning that Return on Assets has a positive but not significant effect on the stock price of PT. Mayora Indah, Tbk. While the results of the calculation of the F-test 0.072 <F table 19.00, it means that Net Profit Margin and Return on Assets have a positive but not significant effect on stock prices at PT. Mayora Indah, Tbk.